2008
DOI: 10.3171/foc.2008.25.11.e14
|View full text |Cite
|
Sign up to set email alerts
|

Protection and repair of the injured spinal cord: a review of completed, ongoing, and planned clinical trials for acute spinal cord injury

Abstract: Over the past 2 decades, advances in understanding the pathophysiology of spinal cord injury (SCI) have stimulated the recent emergence of several therapeutic strategies that are being examined in Phase I/II clinical trials. Ten randomized controlled trials examining methylprednisolone sodium succinate, tirilizad mesylate, monosialotetrahexosylganglioside, thyrotropin releasing hormone, gacyclidine, naloxone, and nimodipine have been completed. Although the primary outcomes in these trials were laregel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
114
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 211 publications
(118 citation statements)
references
References 151 publications
(156 reference statements)
1
114
0
3
Order By: Relevance
“…The ultrastructure of hydrogel was investigated using SEM. Representative micrographs showed that the macroporous hydrogel had communicating pores (2 3 10 6 pores per cm 3 ) with an average size of 80 mm and a specific pore volume of 0.45 (Figure 1c, d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultrastructure of hydrogel was investigated using SEM. Representative micrographs showed that the macroporous hydrogel had communicating pores (2 3 10 6 pores per cm 3 ) with an average size of 80 mm and a specific pore volume of 0.45 (Figure 1c, d).…”
Section: Resultsmentioning
confidence: 99%
“…Clinical treatment may involve intravenous administration of the steroid methylprednisolone; however, the efficacy of this approach has been widely disputed 1 . Several clinical trials have also been completed using pharmacological agents 2,3 ; however, no trials have shown effective regulation of axonal regeneration. Tissue engineering techniques, which are focused on promoting the regeneration of injured nervous tissue, continue to assume greater importance in neuroscience.…”
mentioning
confidence: 99%
“…Economic data from the United States National Institute of Neurological Disorders and Stroke reports that approximately $4 billion dollars are spent annually in the acute treatment and chronic care of spinal cord injured individuals [4]. In spite of the immense impact of SCI at a personal and societal level, uniform treatment strategies aimed at attenuating the initial degree of neurologic injury and reducing patients' future dependency are lacking [5].…”
Section: Introductionmentioning
confidence: 99%
“…Fagan et al 2010;Gupta and Chauhan 2011) as well as spinal cord and traumatic brain injury (e.g. Wang et al 2006;Hawryluk et al 2008). It is concluded that the cytoprotective capability of minocycline results from its anti-inflammatory, anti-apoptotic, and antioxidant properties (e.g.…”
Section: Introductionmentioning
confidence: 99%